Bystander responses and xenophobic mobilization - Robert Braun; Ruud Koopmans (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Students of social movements have long struggled with the question how relatively abstract political opportunities, such as elite divisions, affect unorganized activists without much knowledge of politics. We argue that the relationship between institutional opportunities and decisions to mobilize may take the form of trickle-down politics. In this view activists are affected by political opportunities indirectly through the changes that political developments bring about in the immediate social setting in which they protest. The overall political climate determines the distance between general public opinion and activists' view on society. The smaller this distance the more likely it becomes that activists receive positive feedback from their immediate environment, which in turn results in further mobilization. In particular, we investigate how extreme right activists are influenced by bystander responses that are evoked by the wider political context. Time-series analysis and event history models indeed indicate that spatiotemporal fluctuations in political opportunities and public sentiments are translated into mobilization after activists receive feedback from local bystanders. This suggests that bystander responses, a research topic that has only received scant scholarly attention, play a crucial role in linking political opportunities to mobilization. – – Die soziale Bewegungsforschung setzt sich seit langem mit der Frage auseinander, auf welche Weise sich relativ abstrakte politische Gelegenheiten, wie Meinungsdivergenzen innerhalb von Eliten auf unorganisierte Aktivisten mit begrenzten Politikkenntnissen auswirken. Die Autoren vertreten die Ansicht, dass sich politische Gelegenheiten über einen Trickle-Down-Effekt in Mobilisierungsentscheidungen umsetzen können, indem sie von oben nach unten in das unmittelbare soziale Umfeld der Aktivisten durchsickern und diese somit indirekt beeinflussen. Das politische Klima insgesamt bestimmt die Distanz zwischen der allgemeinen öffentlichen Meinung und der Sicht der Aktivisten auf die Gesellschaft. Je geringer die Distanz ist, um so wahrscheinlicher wird es, dass Aktivisten positives Feedback aus ihrem unmittelbaren Umfeld erhalten, was sich in weiterer Mobilisierung niederschlägt. In dem vorliegenden Paper wird untersucht, wie rechtsextreme Aktivisten durch das Echo von bei ausländerfeindlichen Gewaltaktionen anwesendem Publikum (bystanders) beeinflusst werden, das sich aus einem größeren politischen Kontext ableitet. Mittels Zeitreihenanalysen und Ereignisdatenmodellen zeigen die Analysen, dass zeitliche und räumliche Schwankungen von politischen Gelegenheiten und öffentlicher Meinung in Mobilisierung umschlagen, nachdem Aktivisten vom Publikum aus ihrem lokalen Umfeld Feedback erhalten.
Keywords: 300; ethnic violence; social movements; opportunity structures; structure-agency debates; Germany